2020
DOI: 10.1186/s13054-020-02858-x
|View full text |Cite
|
Sign up to set email alerts
|

The clinical relevance of oliguria in the critically ill patient: analysis of a large observational database

Abstract: Background: Urine output is widely used as one of the criteria for the diagnosis and staging of acute renal failure, but few studies have specifically assessed the role of oliguria as a marker of acute renal failure or outcomes in general intensive care unit (ICU) patients. Using a large multinational database, we therefore evaluated the occurrence of oliguria (defined as a urine output < 0.5 ml/kg/h) in acutely ill patients and its association with the need for renal replacement therapy (RRT) and outcome. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…These discrepancies with our study could be explained by (1) nonstandardized UO assessment and different management of missing values, (2) distinct populations with a higher prevalence of medical patients and respiratory issues, and (3) differences in fluid management leading to different incidence of AKI. 9 Nevertheless, on multivariate analyses, UO criteria were also found to be an independent risk factor for 90-day mortality (OR, 2.89; 95% CI, 1.96-4.25; P < .001).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These discrepancies with our study could be explained by (1) nonstandardized UO assessment and different management of missing values, (2) distinct populations with a higher prevalence of medical patients and respiratory issues, and (3) differences in fluid management leading to different incidence of AKI. 9 Nevertheless, on multivariate analyses, UO criteria were also found to be an independent risk factor for 90-day mortality (OR, 2.89; 95% CI, 1.96-4.25; P < .001).…”
Section: Discussionmentioning
confidence: 92%
“… 4 Most studies reporting AKI outcomes have solely relied on sCr criteria or have applied modified/simplified UO criteria. 2 , 5 , 6 , 7 , 8 , 9 Indeed, sCr levels are regularly monitored in hospitalized patients and can easily be retrieved through electronic medical records. Hence, sCr-based staging is straightforward and can even trigger bedside e-alerts.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with oliguria classified as AKI stage 2, isolated oliguria was common and lower levels of U‐Cystatin C and NGAL were found. Although little is known about the clinical relevance of oliguric renal failure in COVID‐19, several studies have investigated oliguria in the ICU and found that both duration and severity of oliguria is associated with increased risk of end‐stage renal disease and death 16‐18 but not in parity with the Creatinine criteria 19 . This strengthen the notion that these pathways also benefit exploration individually.…”
Section: Discussionmentioning
confidence: 93%
“…When urine output is considered, whether or not it is associated with an increase in serum creatinine, a higher number of AKI cases are diagnosed, and the detection can be made earlier [ 19 ]. The duration of oliguria appears to be associated with the beginning of dialysis and an increased risk of death [ 23 ]. The definition of oliguria has recently received critical appraisal: the impact of both the volume of urine as well as the duration of oliguria on AKI prediction is controversial: KDIGO Clinical Practice Guidelines for Acute Kidney Injury [ 24 ] define a urine output < 0.5 ml/kg/h for > 6 h as AKI stage 1, < 0.5 ml/kg/h for > 12 h as AKI stage 2, and a < 0.3 ml/kg/h for 24 h or anuria for 12 h as AKI stage 3.…”
Section: Discussionmentioning
confidence: 99%